VD_FINDINFO Décision / 2011 / 624 vom 15. Oktober 2011 - VD Tribunal cantonal (2011)
RISQUE DE FUITE, RISQUE DE RÉCIDIVE, RISQUE DE COLLUSION, DÉTENTION PRÉVENTIVE | 221 al. 1 let. a CPP (CH), 221 al. 1 let. b CPP (CH), 221 al. 1 let. c CPP (CH), 393 CPP (CH)